Making sense of the data on Ireland's inward FDI - Frank Barry; Clare O'Mahony (University College Dublin, UCD School of Economics, 2006)
Ireland, in employment terms, is the most FDI-intensive economy in the EU. International comparisons of trends and levels of FDI intensity are usually based on balance-of-payments data however, and the international data series on Ireland's inward FDI tell hugely conflicting stories. Such series are published by the IMF, UNCTAD, OECD and Eurostat (with data generally provided either by the CSO or the IDA), while data on US FDI in Ireland are published by the US Bureau of Economic Analysis. The present paper documents these conflicting stories and searches for any underlying consistency through analysis of the items that the various databases include and exclude. FDI stock, flow and sectoral allocation data are explored and trends contrasted with what is known from MNC employment data.
hdl:10197/1320
Keywords: 330